SoCIAL – training cognition in schizophrenia: a pilot study - Palumbo D (Dove Medical Press, 2017)
Davide Palumbo,* Armida Mucci,* Giuseppe Piegari, Valentina D’Alise, Annapaola Mazza, Silvana Galderisi Department of Psychiatry, University of Campania Luigi Vanvitelli, Naples, Italy *These authors contributed equally to this work Abstract: The purpose of this pilot study was to assess the efficacy of a new social cognition (SC) remediation intervention, the Social Cognition Individualized Activities Lab (SoCIAL), for subjects with schizophrenia. The training includes a module for emotion recognition and one for theory of mind. A comparison with a validated cognitive remediation intervention, the Social Skills And Neurocognitive Individualized Training (SSANIT), was conducted to verify the efficacy of the SoCIAL in improving SC. Ten stabilized patients with schizophrenia accepted to participate. Five patients were randomized to SoCIAL and five to SSANIT. The SoCIAL intervention includes individual sessions of neurocognitive individualized training (NIT) and group sessions of SC training. SSANIT includes individual sessions of NIT and group sessions of social skills individualized training. The interventions were matched for the overall treatment duration (20 weeks) and for the frequency of the sessions (two times a week, one for SoCIAL or social skills individualized training and one for NIT, with a duration of 80 minutes for each session). Results showed a significant treatment effect (effect size: Cohen’s d 0.32) on the primary outcome; in fact, only the SoCIAL intervention improved theory of mind. Patients receiving the SoCIAL intervention also showed an improvement of avolition. These preliminary findings support further development of the SoCIAL and suggest that cognitive remediation should include an SC module. Keywords: cognitive remediation, psychiatric rehabilitation, negative symptoms, avolition, MATRICS consensus cognitive battery, MCCB